The Impact of Digital Transformation on Reducing Cyber Risks: An Applied Study on the Saudi Water Authority (The International Journal for Scientific Research, 2024)
This study aims to identify the impact of digital transformation on reducing cyber risks through an applied study on the Saudi Water Authority. The study employed a descriptive-analytical approach to collect and analyse data, with a sample of 350 employees from the authority. The study covered the dimensions of digital transformation, including activities related to administrative processes, banking procedures, human resources, and customer-related activities. The results showed that digital transformation significantly contributes to reducing cyber risks, such as cyberattacks, data loss, and electronic fraud. It was found that digital transformation in its various dimensions helps enhance cybersecurity and improve the authority's performance in delivering its services. The study recommended strengthening digital transformation by improving the technical infrastructure and providing continuous training for employees to cope with increasing cyber challenges.
Keywords: Digital Transformation; Cyber Risks; Saudi Water Authority; Cybersecurity